Analisis Metode Pemahaman á¸¤adÄ«th Muá¸¥ammad Shaá¸¥rÅ«r dalam Kitab al-Sunnah al-RasÅ«lÄ«yah wa al-Sunnah al-NabawÄ«yah - Arifin, Syamsul (Islamika Inside: Jurnal Keislaman dan Humaniora, 2017)
This article specifically discusses the method and typology of understanding of the á¸¥adÄ«th held by Muá¸¥ammad Shaá¸¥rÅ«r in his work al-Sunnah al-RasÅ«lÄ«yah wa al-Sunnah al-NabawÄ«yah. The results reveal that Shaá¸¥rÅ«r offers a number of stages in understanding á¸¥adÄ«th, are: first, understanding á¸¥adÄ«th not as a divine revelation. Second, understanding á¸¥adÄ«th according to the principles of al-tanzÄ«l al-á¸¥akÄ«m. Third, distinguishing the role of the Prophet Muhammad as an ordinary man, a prophet, and an apostle. Fourth, collecting á¸¥adÄ«ths which are meaningful or still in one theme. Fifth, testing á¸¥adÄ«th with ratio, healthy logic, and science. Sixth, testing á¸¥adÄ«th with the historical fact, and seventh, distinguishing the unseen and the seen. Furthermore, the typology of the understanding hadis of Shahrur in his book can be classified into a moderate-reformist school. This is because he invites Muslims to reconstruct the understanding of á¸¥adÄ«th contextually.